Carbonization reinforced steel slag concrete and preparation method thereof

Through the preparation of modified steel slag and the use of composite water-reducing agents, the deficiencies of steel slag concrete in terms of stability, construction performance and durability are solved, and large, safe and effective resource utilization of steel slag is achieved.

CN119330670AActive Publication Date: 2025-01-21CSCEC WESTERN CONSTR XINJIANG CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411520949.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-21
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The existing steel slag concrete has shortcomings in stability, construction performance and durability, resulting in limited application in the field of building materials.

Method used

By adding steel slag to the culture solution containing iron-oxidizing bacteria, and carrying out shaking culture and drying under the condition of introducing CO2, modified steel slag is prepared, and combined with the use of composite water-reducing agent, carbonization-strengthened steel slag concrete is prepared.

Benefits of technology

This method effectively reduces the f-CaO and f-MgO content in steel slag, improves the stability and construction performance of concrete, enhances its carbonation resistance, and achieves large, safe and effective resource utilization of steel slag.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The steel slag carbonization reinforced concrete is prepared from the following components in parts by weight: 250 to 350 parts of ordinary Portland cement, 50 to 150 parts of fly ash, 50 to 100 parts of mineral powder, 30 to 50 parts of silica fume, 650 to 850 parts of modified steel slag, 950 to 1100 parts of stone, 5 to 10 parts of a composite water reducing agent and 140 to 170 parts of water, wherein the modified steel slag is obtained by adding steel slag into a culture solution containing iron oxidizing bacteria, carrying out shake culture under the condition of introducing CO2, and drying. The steel slag is modified by adopting a metabolic mechanism and a carbonization means of iron-oxidizing bacteria, and the composite water reducer is combined, so that the stability, the construction performance, the durability and the like of the steel slag concrete can be effectively considered while large-dosage resource utilization of the steel slag is realized, and the steel slag concrete has remarkable economic and environmental benefits and is suitable for popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to steel slag carbonization reinforced concrete and a preparation method thereof. Background Art

[0002] With the widespread application of concrete in the construction field, sand and gravel resources, as natural aggregates of concrete, have become increasingly scarce, causing a series of environmental problems; it is urgent to further find suitable substitutes for coarse and fine aggregates in concrete.

[0003] With the rapid development of industrialization, there are problems such as large-scale dumping of industrial waste slag. Industrial waste slag mainly includes steel slag, lithium slag, slag, etc. Among them, the surface of steel slag is loose and porous, with high hardness and good wear resistance, and has similar properties to sand and gravel aggregates. However, these steel slags are not well utilized at present, and even some waste steel slags are directly dumped in farmland, causing environmental pollution. It is imperative to study the use of steel slag to replace coarse and fine aggregates in concrete.

[0004] At present, steel slag aggregate and steel slag powder have been studied in the field of building materials. However, due to its poor stability, it is easy to cause concrete surface damage or structural damage, which limits the large-scale use of steel slag. At room temperature, f-CaO and f-MgO in steel slag are very easy to hydrate, resulting in volume expansion, which seriously affects the application of steel slag in the field of building materials; in addition, the construction performance of steel slag concrete is poor, which can easily lead to difficulties in concrete pumping, large shrinkage, and shrinkage cracks. Summary of the invention

[0005] The main purpose of the present invention is to provide a carbonized reinforced steel slag carbon concrete in response to the problems and shortcomings of the prior art. While realizing the resource utilization of large amounts of steel slag, the present invention can effectively take into account the stability, construction performance and durability of steel slag concrete, has significant economic and environmental benefits, and is suitable for promotion and application.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A steel slag carbonization reinforced concrete, the components and their weight proportions include: 250-350 parts of ordinary Portland cement, 50-150 parts of fly ash, 50-100 parts of mineral powder, 30-50 parts of silica fume, 650-850 parts of modified steel slag, 950-1100 parts of stone, 5-10 parts of composite water reducing agent, and 140-170 parts of water; wherein the modified steel slag is obtained by adding steel slag to a culture solution containing iron oxidizing bacteria, and carrying out oscillation culture and drying under the condition of passing CO2.

[0008] Furthermore, the specific preparation steps of the modified steel slag include: taking 1.5-2 kg of steel slag, drying it, adding 11-15 L of culture solution containing iron-oxidizing bacteria, introducing CO2, performing shaking culture, and finally drying to obtain modified steel slag.

[0009] In the above scheme, the flow rate of the CO2 is 1500-2500 sccm; the purity of the CO2 gas is 97-99.5 vol%.

[0010] In the above scheme, the drying temperature is 100-115° C. and the time is 1.5-2 hours.

[0011] In the above scheme, the shaking culture step adopts a temperature of 23-25°C, an shaking rate of 150-200 r / min, and a time of 10d-11d.

[0012] Preferably, during the shaking culture process, the culture solution containing iron-oxidizing bacteria is replaced with an equal amount of new culture solution every 286 to 290 hours.

[0013] In the above scheme, the obtained modified steel slag is stored in an environment with a temperature of 20-25° C. and a humidity of not less than 50%.

[0014] In the above scheme, the steps of preparing the culture solution containing iron-oxidizing bacteria include:

[0015] 1) In the culture medium, the main components and their weight proportions include: 0.2-1.5 parts of CaCl2·2H2O, 0.5-1.0 parts of KH2PO4·3H2O, 0.5-1.0 parts of NaNO3, 0.5-1.2 parts of (NH4)2SO4, 0.5-1.2 parts of MgSO4·7H2O, 10-15 parts of ammonium ferric citrate (FeC6H5O7·NH4OH), and 100-110 parts of water;

[0016] Dissolve the weighed components in water (100-110 parts), adjust the pH value to 6.9-7.1 with NaOH solution, gradually add 20-30 parts of agar powder under heating conditions (95-100°C), and stir continuously to prevent the bottom from sticking; when the agar is completely dissolved and the culture solution is viscous and solidifiable, sterilize and cool to room temperature (20-25°C) to obtain a culture medium;

[0017] 2) Take an iron block and soak it in water. After the rust layer falls off, use a glass rod to break the rust layer. Take the water sample and apply it on the culture medium. Invert and culture it in a constant temperature incubator until white filamentous colonies appear on the surface of the culture medium. Pick a single white filamentous fungus and inoculate it in 50-60 mL of new selective culture medium to continue culturing until a reddish-brown circular colony with a diameter of 1-3 mm is formed. Pick a single reddish-brown circular colony and inoculate it again (50-60 mL of culture medium) until the morphology of the subsequent colonies remains unchanged, thus obtaining a culture solution containing iron-oxidizing bacteria.

[0018] Furthermore, in the culture solution containing iron-oxidizing bacteria, the content of iron-oxidizing bacteria is 5 to 30 wt%.

[0019] In the above scheme, the main chemical components in the steel slag and their mass percentages include: CaO 35-37%, iron oxide content 30-35%, SiO2 8-10%, Al2O3 2-5%.

[0020] Furthermore, in the iron oxide, the content of FeO is 5-10wt%.

[0021] Furthermore, the content of free calcium oxide in the steel slag is 4-6%.

[0022] In the above scheme, the preparation method of the composite water reducing agent comprises:

[0023] 1) Weighing a polyether macromonomer and potassium methyl silicate and mixing them evenly to obtain a base liquid;

[0024] 2) mixing acetic acid, thioglycolic acid and water evenly to obtain a mixed solution I; mixing hydroxypropionic acid and water evenly to obtain a mixed solution II;

[0025] 3) Add the obtained mixed solution I and mixed solution II dropwise into the base solution, and add hydrogen peroxide and stabilizer while adding, and stir after the addition is completed to obtain the composite water reducing agent.

[0026] In the above scheme, the polyether macromonomer can be selected from one or more of allyl polyoxyethylene ether, methyl allyl polyoxyethylene ether and the like.

[0027] Furthermore, the molecular weight of the polyether macromonomer is 1500-2400.

[0028] In the above scheme, the main raw materials of the composite water reducer and their weight proportions include: 20-35 parts of polyether macromonomer, 12-25 parts of potassium methyl silicate, 2-5 parts of acetic acid, 2-5 parts of thioglycolic acid, 2-5 parts of hydroxypropionic acid, 10-20 parts of hydrogen peroxide, and 2-8 parts of stabilizer.

[0029] Furthermore, the concentration of the hydrogen peroxide solution is 6-10 vol%.

[0030] Furthermore, the stabilizer may be ammonium persulfate or sodium persulfate, etc., which can promote continuous polymerization reaction and effectively improve the problem of slow reaction after the introduction of potassium methyl silicate.

[0031] In the above scheme, the effective solid content of the composite water reducing agent is 11-14%.

[0032] In the above scheme, the mixed solution I and the mixed solution II are dripped using a peristaltic meter at a dripping rate of 1.5 to 3.0 g / min.

[0033] In the above scheme, the stirring treatment time in step 3) is 30 to 45 minutes.

[0034] The above-mentioned method for preparing steel slag carbonization reinforced concrete comprises the following steps:

[0035] 1) Weigh the raw materials according to the proportion, and the components and their weight proportions include: 250-350 parts of ordinary Portland cement, 50-150 parts of fly ash, 50-100 parts of mineral powder, 30-50 parts of silica fume, 650-850 parts of modified steel slag, 950-1100 parts of stone, 5-10 parts of composite water reducing agent, and 140-170 parts of water;

[0036] 2) Firstly, ordinary Portland cement, fly ash, mineral powder, silica fume, modified steel slag and stone are added for a first stirring process, then part of water is added for a second stirring process, and the remaining water and composite water reducing agent are added for a third stirring process to obtain a steel slag carbonization strengthened concrete mixture;

[0037] 3) Forming and curing: pouring, vibrating and forming; stopping, removing the mould and curing in a curing room to obtain the steel slag carbonization strengthened concrete.

[0038] In the above scheme, in step 2), 1 / 3 to 1 / 2 of the amount of water is first added.

[0039] In the above scheme, the first stirring treatment time in step 2) is 20 to 30 seconds, the second stirring time is 30 to 50 seconds, and the third stirring time is 60 to 120 seconds.

[0040] In the above scheme, the vibration time is 30 to 90 seconds.

[0041] Preferably, before vibrating, the material is manually rammed clockwise from the outside to the inside, and struck in all directions around it with a rubber hammer.

[0042] In the above scheme, the static process conditions include: temperature of 20-25°C, humidity of more than 50%, and time of 24-32 hours.

[0043] The steel slag carbonization reinforced concrete prepared according to the above scheme has a concrete slump of 200-230 mm, an expansion of 580-630 mm, a 28-day compressive strength of 35-60 MPa, and a 3-day concrete shrinkage of 50-100×10 -6 , the carbonization depth at 28 days is 0.1~0.9mm.

[0044] The principle of the present invention is:

[0045] The present invention utilizes the metabolic mechanism of iron oxidizing bacteria to efficiently modify steel slag, oxidizes part of the +2-valent iron in the steel slag to +3-valent iron, improves the adsorption capacity of CO2, and simultaneously improves the surface hardness and strength of the steel slag through carbonization, which can improve the strength of the steel slag cementitious material, promote the dissolution of calcium and magnesium ions in the steel slag, reduce the content of f-CaO and f-MgO in the steel slag, and provide suitable conditions for the mineralization reaction. The microbial modification technology is combined with the indirect carbon fixation technology of steel slag leaching (immersing in a carbon dioxide-containing solution for carbonization) to achieve the dual purposes of modification and rapid carbon fixation.

[0046] The present invention uses polyether macromonomer and potassium methyl silicate as main raw materials to prepare a composite water reducing agent, which is used to prepare steel slag concrete. On the basis of ensuring good water reducing performance, the surface tension of steel slag can be effectively increased (the surface tension of steel slag-based aggregate can be enhanced when in contact with water, and the water absorption rate of aggregate can be reduced), the water absorption rate of steel slag-based aggregate can be reduced, the working performance of steel slag concrete can be optimized, the unstable factors of steel slag can be eliminated, the gelling property can be improved, and the high added value utilization of steel slag waste can be realized.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] 1) The modified steel slag of the present invention can effectively reduce the content of f-CaO and f-MgO in the steel slag, eliminate the unstable factors of the steel slag, improve its stability, and can be carbonized and strengthened by CO2, having the dual effects of modification and carbon fixation;

[0049] 2) The composite water reducing agent of the present invention can effectively improve the problems of high water absorption rate on the surface of steel slag and poor concrete working performance, improve the concrete paste value, and increase the fluidity and encapsulation of concrete;

[0050] 3) The steel slag concrete obtained by the present invention has the advantages of low shrinkage, good stability, excellent surface performance, enhanced carbonation resistance, etc.; it can realize the high added value resource utilization of steel slag, and has significant environmental and economic benefits. DETAILED DESCRIPTION

[0051] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0052] In the following embodiments, the specific preparation steps of the modified steel slag are as follows: take 2 kg of steel slag, dry it, introduce CO2 into 15 L of culture solution containing iron oxidizing bacteria, perform oscillation culture, and finally dry it to obtain modified steel slag; the flow rate of the CO2 introduction is 20000 sccm; the purity of the CO2 gas is 99.5 vol%; the drying temperature is 105°C and the time is 2h; the temperature used in the oscillation culture step is 25°C, 200r / min, and the time is 20d.

[0053] The steel slag used was provided by Xinjiang Bayi Iron and Steel Co., Ltd. of Baosteel Group, and had a CaO content of 36% (including 5% free calcium oxide), an iron oxide content of 34%, an SiO2 content of 8%, and an Al2O3 content of 3%.

[0054] In the following examples, the steps for preparing the culture solution containing iron-oxidizing bacteria include:

[0055] 1) Weigh each component according to the culture medium formula, wherein each component and its weight proportion are: 1.0 part of CaCl2·2H2O, 0.5 part of KH2PO4·3H2O, 0.5 part of NaNO3, 1.2 parts of (NH4)2SO4, 1.2 parts of MgSO4·7H2O, 12 parts of ammonium ferric citrate (FeC6H5O7·NH4OH), and 100 parts of distilled water; add each weighed component into water to dissolve, adjust the pH value to 7.0 with NaOH solution, gradually add 30 parts of agar powder into the water under heating condition of 100° C., and stir continuously to prevent the bottom from sticking; when the agar is completely dissolved and the culture medium is in a viscous and solidifiable state, sterilize, cool to room temperature 20° C., and obtain the culture medium;

[0056] 2) Take an iron block and soak it in water. After the rust layer falls off, use a glass rod to break the rust layer. Take the water sample and apply it on the culture medium. Invert and culture it in a constant temperature incubator at 25°C until white filamentous colonies appear on the surface of the culture medium. Pick a single white filamentous bacteria and inoculate it into the new culture medium for continued cultivation. After 2 days, the colony covers the surface of the culture medium and gradually grows into a reddish-brown circular colony. Pick a single reddish-brown circular colony and inoculate it into the new culture medium again until the morphology of the subsequent colonies remains unchanged, thereby obtaining a culture solution containing iron-oxidizing bacteria, and the iron-oxidizing bacteria content is 20wt%.

[0057] In the following examples, the preparation steps of the composite water reducer used are as follows: 30 parts of a polyether macromonomer (allyl polyoxyethylene ether, molecular weight 1800) are weighed and mixed with 20 parts of potassium methyl silicate to obtain a base liquid; 5 parts of acetic acid, 3 parts of thioglycolic acid and 100 parts of water are mixed to obtain a mixed solution I; 2 parts of hydroxypropionic acid and 50 parts of water are mixed to obtain a mixed solution II; the obtained mixed solution I and the mixed solution II are added dropwise to the base liquid, using a peristaltic meter with a drop acceleration rate of 2 g / min, and 15 parts of hydrogen peroxide (concentration 8%) and 5 parts of a stabilizer (ammonium persulfate) are added while dropping, and stirring is performed after the dropwise addition is completed. The stirring treatment time is 45 min, and the composite polycarboxylate water reducer is obtained.

[0058] Example 1

[0059] A steel slag carbonization reinforced concrete, the components and their weight proportions include: 350 parts of ordinary Portland cement, 120 parts of fly ash, 80 parts of mineral powder, 30 parts of silica fume, 700 parts of modified steel slag, 980 parts of stone, 8 parts of composite water reducing agent, and 150 parts of water; the specific preparation method includes the following steps:

[0060] First, ordinary Portland cement, fly ash, mineral powder, silica fume, modified steel slag and stone are added for a stirring process for 30 seconds, 1 / 2 amount of water is added for a second stirring process for 50 seconds, and the remaining water and composite water reducing agent are added for a third stirring process for 120 seconds to obtain a steel slag carbonization strengthened concrete mixture; molding and curing: pouring, vibrating, molding, standing for 24 hours, removing the mold and curing in a curing room to obtain the steel slag carbonization strengthened concrete; the performance test results are shown in Table 1.

[0061] Table 1 Concrete performance test results obtained in Example 1

[0062] 28d compressive strength Slump Expansion Shrinkage 28d Carbonization Depth 58MPa 225mm 620mm <![CDATA[85×10 -6 ]]> 0.2mm

[0063] Example 2

[0064] A steel slag carbonization reinforced concrete, the components and their weight proportions include: 350 parts of ordinary Portland cement, 120 parts of fly ash, 80 parts of mineral powder, 30 parts of silica fume, 850 parts of modified steel slag, 950 parts of stone, 10 parts of composite water reducing agent, and 150 parts of water; the preparation method thereof comprises the following steps:

[0065] First, add ordinary Portland cement, fly ash, mineral powder, silica fume, modified steel slag, and stone for a stirring process for 30 seconds, add 1 / 2 amount of water for a second stirring process for 50 seconds, add the remaining water and composite water reducer for a third stirring process for 120 seconds, and obtain the steel slag carbonization strengthened concrete mixture; molding and curing: pouring, vibrating, molding, standing for 24 hours, removing the mold and putting it in the curing room for curing, and the steel slag carbonization strengthened concrete is obtained. The performance test results are shown in Table 2:

[0066] Table 2 Concrete performance test results obtained in Example 2

[0067] 28d compressive strength Slump Expansion Shrinkage 28d Carbonization Depth 52MPa 230mm 630mm <![CDATA[95×10 -6 ]]> 0.4mm

[0068] Example 3

[0069] A steel slag carbonization reinforced concrete, the components and their weight proportions include: 350 parts of ordinary Portland cement, 120 parts of fly ash, 80 parts of mineral powder, 30 parts of silica fume, 700 parts of modified steel slag, 980 parts of stone, 8 parts of composite water reducing agent, and 150 parts of water; the preparation method thereof comprises the following steps:

[0070] First, add ordinary Portland cement, fly ash, mineral powder, silica fume, modified steel slag, and stone for a stirring process for 20 seconds, add 1 / 3 of the amount of water for a second stirring process for 30 seconds, add the remaining water and composite water reducer for a third stirring process for 60 seconds, and obtain the steel slag carbonization strengthened concrete mixture; molding and curing: pouring, vibrating, molding, standing for 24 hours, removing the mold and putting it in the curing room for curing, and the steel slag carbonization strengthened concrete is obtained. The performance test results are shown in Table 3:

[0071] Table 3 Concrete performance test results obtained in Example 3

[0072] 28d compressive strength Slump Expansion Shrinkage 28d Carbonization Depth 56MPa 210mm 585mm <![CDATA[80×10 -6 ]]> 0.5mm

[0073] Comparative Example 1

[0074] A steel slag concrete, wherein the components and their weight proportions include: 350 parts of ordinary Portland cement, 120 parts of fly ash, 80 parts of mineral powder, 30 parts of silica fume, 700 parts of steel slag, 980 parts of stone, 8 parts of composite water reducing agent, and 150 parts of water; the steel slag is provided by East Hope Group Co., Ltd., and has a calcium oxide content of 35% (including 5.1% of free calcium oxide), a ferric oxide content of 35%, a silicon oxide content of 9%, and an aluminum oxide content of 3.2%; and the preparation method thereof comprises the following steps:

[0075] First, add ordinary Portland cement, fly ash, mineral powder, silica fume, steel slag and stone for a stirring process for 30 seconds, add 1 / 2 amount of water for a second stirring process for 50 seconds, add the remaining water and composite water reducer for a third stirring process for 120 seconds to obtain a steel slag concrete mixture; molding and curing: pouring, vibrating, molding, standing for 24 hours, removing the mold and curing in the curing room to obtain steel slag concrete; the performance test results are shown in Table 4.

[0076] Table 4 Concrete performance test results obtained in Comparative Example 1

[0077] 28d compressive strength Slump Expansion Shrinkage 28d Carbonization Depth 35MPa 160mm 570mm <![CDATA[-235×10 -6 ]]> 12mm

[0078] Comparative Example 2

[0079] A steel slag concrete, wherein the components and their weight proportions include: 350 parts of ordinary Portland cement, 120 parts of fly ash, 80 parts of mineral powder, 30 parts of silica fume, 850 parts of modified steel slag, 830 parts of stone, 10 parts of ordinary high-performance water reducer, and 150 parts of water; the water reducer used is the PCA-06 standard polycarboxylate water reducer provided by Urumqi Kehuida Chemical Building Materials Co., Ltd., and its solid content is 12.5% ​​and the water reduction rate is 25%; the preparation method of the steel slag concrete comprises the following steps:

[0080] First, ordinary Portland cement, fly ash, mineral powder, silica fume, modified steel slag and stone are added for a stirring process for 30 seconds, 1 / 2 amount of water is added for a second stirring process for 50 seconds, and the remaining water and composite water reducing agent are added for a third stirring process for 120 seconds to obtain a steel slag concrete mixture; molding and curing: pouring, vibrating, molding, standing for 24 hours, removing the mold and curing in a curing room to obtain the steel slag concrete; the performance test results are shown in Table 2:

[0081] Table 5 Concrete performance test results obtained in Comparative Example 2

[0082] 28d compressive strength Slump Expansion Shrinkage 28d Carbonization Depth 45MPa 200mm 590mm <![CDATA[115×10 -6 ]]> 1.5mm

[0083] Comparative Example 3

[0084] A steel slag concrete, wherein the components and their weight proportions include: 350 parts of ordinary Portland cement, 120 parts of fly ash, 80 parts of mineral powder, 30 parts of silica fume, 700 parts of oxidized / carbonized steel slag, 980 parts of stone, 8 parts of composite water reducer, and 150 parts of water; wherein the preparation method of the oxidized modified steel slag is: take 500g of steel slag in a vacuum box, treat it under a negative pressure of -70MPa for 1h, then add 100ml of hydrogen peroxide under normal atmospheric pressure, soak it in a vacuum box for 6h, then take out the steel slag and put it in water, introduce CO2 into the water, and the flow rate of CO2 is 20000sccm; the purity of CO2 gas is 99.5vol%, and the time is 20d, so as to obtain the oxidized / carbonized steel slag;

[0085] The preparation method of the steel slag concrete comprises the following steps:

[0086] First, add ordinary Portland cement, fly ash, mineral powder, silica fume, oxidized / carbonized steel slag, and stone for a stirring process for 20 seconds, add 1 / 3 of the amount of water for a second stirring process for 30 seconds, add the remaining water and composite water reducer for a third stirring process for 60 seconds, and obtain the steel slag carbonization reinforced concrete mixture; molding and curing: pouring, vibrating, molding, standing for 24 hours, removing the mold and putting it in the curing room for curing, and the steel slag concrete is obtained. The performance test results are shown in Table 3:

[0087] Table 6 Concrete performance test results obtained in Comparative Example 3

[0088] 28d compressive strength Slump Expansion Shrinkage 28d Carbonization Depth 42MPa 180mm 565mm <![CDATA[102×10 -6 ]]> 5mm

[0089] Comparative Example 4

[0090] A steel slag concrete, wherein the components and their weight proportions include: 350 parts of ordinary Portland cement, 120 parts of fly ash, 80 parts of mineral powder, 30 parts of silica fume, 850 parts of modified steel slag, 950 parts of stone, 150 parts of water, and 10 parts of a water reducer, wherein the water reducer is prepared in the following steps: 50 parts of a polyether macromonomer (allyl polyoxyethylene ether, molecular weight 1800) is used as a base liquid; 5 parts of acetic acid, 3 parts of thioglycolic acid and 100 parts of water are mixed evenly to obtain a mixed liquid I; 2 parts of hydroxypropionic acid and 50 parts of water are mixed evenly to obtain a mixed liquid II; the obtained mixed liquid I and mixed liquid II are dripped into the base liquid, a peristaltic instrument is used, the dripping rate is 2.5 g / min, and 15 parts of hydrogen peroxide (concentration 8%) are added while dripping, and stirring is performed after the dripping is completed, and the stirring treatment time is 45 minutes, so as to obtain the polycarboxylic acid water reducer;

[0091] The concrete preparation method comprises the following steps:

[0092] First, add ordinary Portland cement, fly ash, mineral powder, silica fume, modified steel slag, and stone for a stirring process for 30 seconds, add 1 / 2 amount of water for a second stirring process for 50 seconds, add the remaining water and composite water reducer for a third stirring process for 120 seconds, and obtain the steel slag carbonization strengthened concrete mixture; molding and curing: pouring, vibrating, molding, standing for 24 hours, removing the mold and putting it into the curing room for curing, and then obtain the steel slag concrete. The performance test results are shown in Table 2:

[0093] Table 2 Concrete performance test results obtained in Example 2

[0094] 28d compressive strength Slump Expansion Shrinkage 28d Carbonization Depth 48MPa 185mm 550mm <![CDATA[325×10 -6 ]]> 6.5mm

[0095] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the invention.

Claims

1. A steel slag carbonization strengthened concrete, characterized in that: The components and their weight proportions include: 250-350 parts of ordinary Portland cement, 50-150 parts of fly ash, 50-100 parts of mineral powder, 30-50 parts of silica fume, 650-850 parts of modified steel slag, 950-1100 parts of stone, 5-10 parts of composite water reducing agent, and 140-170 parts of water; wherein the modified steel slag is obtained by adding steel slag to a culture solution containing iron oxidizing bacteria, and carrying out oscillation culture and drying under the condition of passing CO2.

2. The steel slag carbonization reinforced concrete according to claim 1, characterized in that: The main chemical components in the steel slag and their mass percentages include: CaO 35-37%, iron oxide content 30-35%, SiO2 8-10%, and Al2O3 2-5%.

3. The steel slag carbonization strengthened concrete according to claim 2, characterized in that: In the iron oxide, the content of FeO is 5-10wt%.

4. The steel slag carbonization reinforced concrete according to claim 1, characterized in that: In the culture solution containing iron-oxidizing bacteria, the content of iron-oxidizing bacteria is 5-30wt%.

5. The steel slag carbonization reinforced concrete according to claim 1, characterized in that: The flow rate of the CO2 introduced is 1500-2500 sccm.

6. The steel slag carbonization reinforced concrete according to claim 1, characterized in that: The preparation method of the composite water reducing agent comprises: 1) Weighing a polyether macromonomer and potassium methyl silicate and mixing them evenly to obtain a base liquid; 2) mixing acetic acid, thioglycolic acid and water evenly to obtain a mixed solution I; mixing hydroxypropionic acid and water evenly to obtain a mixed solution II; 3) Add the obtained mixed solution I and mixed solution II dropwise into the base solution, and add hydrogen peroxide and stabilizer while adding, and stir after the addition is completed to obtain the composite water reducing agent.

7. The steel slag carbonization reinforced concrete according to claim 6, characterized in that: The main raw materials of the composite water reducing agent and their weight proportions include: 20-35 parts of polyether macromonomer, 12-25 parts of potassium methyl silicate, 2-5 parts of acetic acid, 2-5 parts of thioglycolic acid, 2-5 parts of hydroxypropionic acid, 10-20 parts of hydrogen peroxide, and 2-8 parts of stabilizer.

8. The steel slag carbonization reinforced concrete according to claim 6, characterized in that: The dropping rate of the mixed solution I and the mixed solution II is 1.5-3.0 g / min.

9. The method for preparing steel slag carbonization reinforced concrete according to any one of claims 1 to 8, characterized in that: The steps include: 1) Weigh the raw materials according to the proportion, and the components and their weight proportions include: 250-350 parts of ordinary Portland cement, 50-150 parts of fly ash, 50-100 parts of mineral powder, 30-50 parts of silica fume, 650-850 parts of modified steel slag, 950-1100 parts of stone, 5-10 parts of composite water reducing agent, and 140-170 parts of water; 2) Firstly, ordinary Portland cement, fly ash, mineral powder, silica fume, modified steel slag and stone are added for a first stirring process, then part of water is added for a second stirring process, and the remaining water and composite water reducing agent are added for a third stirring process to obtain a steel slag carbonization strengthened concrete mixture; 3) Forming and curing: pouring, vibrating and forming; stopping, removing the mould and curing in a curing room to obtain the steel slag carbonization strengthened concrete.

10. The preparation method according to claim 9, characterized in that: In step 2), first add 1 / 3 to 1 / 2 of the amount of water.

Citation Information

Patent Citations

  • Preparation method of modified steel slag for removing arsenic from water body

    CN108031429A

  • Steel slag modifier for roads as well as preparation method and use method of steel slag modifier

    CN118185159A

  • Aqueous tinting base, kit-of-parts tinting system comprising the tinting base, aqueous coating formulation obtained from the kit-of-parts tinting system, and use of the aqueous coating formulation

    EP4389829A1

  • Material and method for treating iron-containing acidic waste water

    JP2004113977A